A participatory experience in environmental education programs in environmental licensing: the implementation of pea barra longa (mg) - Pinto, Vicente Paulo dos Santos; Guimarães, Mauro; Zacarias, Rachel dos Santos; Faria, Jeniffer de Souza; Sobral, Marcela de Marco (Geosaberes; Vol 9 No 18 (2018): May - Aug.DO - 10.26895/geosaberes.v9i18.635, 2018)
This article is about the implantation of a methodological proposal of environmental education (EE) within the process of environmental licensing. It was intended to engender methodological innovations related to elaboration, execution and monitoring processes of EE programmes. This proposal was accomplished by GEA-UFJF in the county of Barra Longa, MG. The educational actions happened in four phases: 1ª) recognition-approximation with local reality; 2ª) participatory planning-diagnosis; 3ª) diffusion / realization of educational / formative processes; 4ª) community mobilization. As outstanding results of experience was contacted an initiative of the participating subjects in structure a Collective aiming the creation of a community association. About the proposed methodological innovations there was a huge investment in the formation of the local dynamizers to face the socio-environmental problems.
Keywords: Geografia, Educação Ambiental, Licenciamento Ambiental